The role of virtual water for sustainable economic restructuring: Evidence from Uzbekistan, Central Asia - Maksud Bekchanov; Anik Bhaduri; Manfred Lenzen; John P.A. Lamers (University of Bonn, Center for Development Research (ZEF), 2012)
Increases in water demand due to population growth, industrial development and urbanization necessitate economically efficient use of water resources worldwide. This is particularly true in the dryland zones of the world relying on irrigated agriculture for economic development such as in Uzbekistan, Central Asia. Due to ill-managed water resources and the dominance of high water intensive crops, water use efficiency in the region is very low. This challenges Uzbekistan to modernize its agricultural sectors and develop its industrial sectors guided by the principles of a green economy, which are the basis for sustainable growth. Therefore, this study aims to prioritize economic sectors according to their sustainable growth potential. To this end, we employ a national inputoutput model to estimate economic backward and forward linkage measures and virtual water contents across the sectors. Our results indicate that developing agro-processing industries and the livestock sector rather than relying on the production of raw agricultural commodities such as cotton, wheat, and rice provides more sustainable economic development in Uzbekistan. However, to exploit these comparative advantages, the necessary market infrastructure and institutions as well as an increased control over wastewaters would need to be implemented.
Keywords: 330; water productivity; input-output model; virtual water content; backward linkage index; forward linkage index; Aral Sea Basin; Wasserpolitik; Bewässerung; Produktivität; Nachhaltige Entwicklung; Wasser; Input-Output; Usbekistan; Aralsee; Zentralasien